Management accounting and risk management in Malaysian financial institutions : an exploratory study - Abdul Rashid, Siti Zaleha; Abdul Rahman, Abdul Rahim; Wan Ismail, Wan Khairuzzaman (Emerald, 2011)
Purpose – The purpose of this paper is to examine the link between management accounting and risk management. The paper measures the extent to which management accounting practices help in managing risks and the extent of the integration between these two important managerial functions. Design/methodology/approach – The study used a mail survey of financial institutions listed in the Malaysian Central Banks’ web site. The respondents to whom 106 questionnaires were sent were the chief financial officers; the response rate was 68 percent. A total of 16 post-survey semi-structured interviews were also conducted with selected respondents to gain further insights into the survey findings. Findings – The findings from the survey indicate that analysis of financial statements was perceived to contribute most towards risk management. The majority of the respondents were of the view that the management accounting function was greatly involved in the organization’s risk management. Consistent with the survey findings, the interviewees also perceived that budgetary control, budgeting, and strategic planning played important roles in managing risk.Research limitations/implications – This is a study conducted in Malaysian financial institutions and thus, results may not be generalizable to other contexts. The findings of this study strengthen the importance of both management accounting and risk management in complementing each other to form part of the corporate performance management systems. Originality/value – This paper contributes to the literature as very few studies have examined the significant link between management accounting and risk management.